Implantação de um biodigestor anáerobio em propriedade rural de Caçapava do Sul - RS - (:unkn) unknown (Universidade Federal do Pampa, 2017)
In recent years there has been a growing demand for alternative sources of energy in order to safeguard the preservation of the planet the planet is fine but you could also say: our planet that has been threatened by the increasing and unbridled usage of fossil fuels.By means of anaerobic digestion, the process of degradation of organic matter by means of microorganisms, in the absence of oxygen, produces two products namely biogas, composed mainly of methane and carbon dioxide, and a liquid normally used as fertilizer which contains minerals and nutrients essential to soil and plants. In this function the implantation of a homemade biodigester on a rural property in Caçapava do Sul -RS with sheep residues, for the production of cooking gas (LPG), and having as by-product the biofertilizer which will be used for the fertilization of the Soil, thus contributing to the development of property, and the preservation of the environment.The project in focus shows the ease of construction and operation of a biodigester. It shows the relation between the climatic variables, mainly the temperature, with the biogas production. The results indicated that to obtain the biogas production the temperature cannot be low, otherwise it will not result in a high time for the gas to be generated.
Keywords: Digestão anaeróbica; Resíduos da ovinocultura; Energia alternativa; Anaerobic Digestion; Sheep residues; Alternative energy; CNPQ::CIENCIAS EXATAS E DA TERRA